Integration of Organic Rankine Cycle with Lignite Flue Gas Pre-drying for Waste Heat and Water Recovery from Dryer Exhaust Gas: Thermodynamic and Economic Analysis. (May 2017) - Han, Xiaoqu; Karellas, Sotirios; Liu, Ming; Braimakis, Konstantinos; Chen, Weixiong; Yan, Junjie; Kakaras, Emmanuel
Abstract: The flue gas pre-drying of lignite produces a moisture rich dryer exhaust gas which can be further cooled to recover the waste heat and water vapor. An environmental friendly power system is investigated in the present work, which integrates the lignite flue gas pre-drying system with an organic Rankine cycle (ORC) to utilize the waste heat to generate power and capture the condensed water. Simulation models of the integrated system are developed, incorporating thermodynamic and economic evaluation indicators. The optimal energy and exergy efficiencies of the ORC system are calculated to be 3.10% and 24.57%, respectively, for an evaporation temperature of 51 °C when R245fa is used as the working fluid. Accordingly, the ORC power output is 3.61 MW and the absolute plant efficiency improvement is 0.27% points. Moreover, 55.17% of the water vapor can be recovered. The economic performance significantly relies on the specific investment cost of ORC and the electricity selling price. Typically, the break-even points of the specific investment cost are 2300 €/kW and 3700 €/kW when electricity selling prices are 0.05 €/kWh and 0.08 €/kWh, respectively.